An Interview with Ian McEwan - Vanessa Guignery (Études Britanniques Contemporaines, 2018)
This interview with Ian McEwan traces his fictional production from his early work published in the 1970s to the novella Nutshell (2016), with discussions of Enduring Love (1997), Saturday (2005), On Chesil Beach (2007) and The Children Act (2014). Ian McEwan talks about his relation to literary tradition, his use of research, his interest in the form of the novella, his love for music and his work as a screenplay writer, among other topics. This is an edited synthesis of two interviews conducted by Vanessa Guignery at the Théâtre des Subsistances in Lyon for the opening of the ‘Assises Internationales du Roman’ organised by the Villa Gillet on 21 May 2018 and at the École Normale Supérieure de Lyon on 22 May 2018. The interviews were transcribed with the very kind help of Diane Gagneret, Natacha Lasorak, Héloïse Lecomte and Julia Siccardi. The editor would like to thank Ian McEwan for kindly and meticulously revising the final written transcript of this interview